Maximum efficiency in the hydroxyl-radical-based self-cleansing of the troposphere - Rohrer, Franz; Lu, Keding; Hofzumahaus, Andreas; Bohn, Birger; Brauers, Theo; Chang, Chih-Chung; Fuchs, Hendrik; Rolf Häseler; Holland, Frank; Min Hu; Kita, Kazuyuki; Kondo, Yutaka; et al. (Nature Geoscience, 2014)
The removal of trace gases from the troposphere is, in most cases, initialized by reactions with hydroxyl radicals, and the products of these reactions are eventually deposited on the Earth's surface. The concentration of these hydroxyl radicals is therefore a measure of atmospheric self-cleansing. In theory, hydroxyl-radical concentrations can be enhanced by the recycling of some of the reaction products. The only known efficient recycling process involves nitrogen oxide and leads to production of ozone, yet observations in regions with high hydrocarbon and low nitrogen oxide concentrations show substantially elevated hydroxyl-radical concentrations, up to ten times higher than expected. If we normalize observed hydroxyl-radical concentrations to the maximum achievable in model calculations with variable nitrogen oxide concentrations, this photochemical coordinate system uncovers a common feature in almost all of these observations: even in the presence of inadequate amounts of nitrogen oxides, hydroxyl-radical concentrations are enhanced to the theoretical maximum obtainable at very much higher nitrogen oxide concentrations. This means that this important part of the self-cleansing capability of the atmosphere is working at maximum efficiency even in regions with a high burden of biogenic hydrocarbons and low nitrogen oxide concentration. Since these processes do not involve nitrogen oxides, tropospheric ozone production is greatly reduced compared with the expectation from current theory.